2019
DOI: 10.15282/jmes.13.4.2019.09.0465
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Savonius blade height on the performance of a hybrid Darrieus-Savonius wind turbine

Abstract: A vertical hybrid turbine commonly consists of a Darrieus and Savonius rotor where the Savonius is inside Darrieus turbine. This paper describes the experimental study of hybrid Darrieus-Savonius wind turbines by variation in Savonius blade height. In this case, the effect of the blade height of the Savonius blade was studied experimentally in a subsonic wind tunnel. The effect of the height of a Savonius blade relative to that of Darrieus called blade height ratios δ was investigated to know the hybrid turbin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…This result is in agreement with Abohela et al [50]. Similar studies by Puspitasari et al [51] shows that they were able to achieved a C p value of 0.20 which indicates 48% increase in the power coefficient. The power coefficient is slightly higher because the operating condition is not the same and the wind speed is 10 m/s as regard to the 4.5 m/s used in this study.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This result is in agreement with Abohela et al [50]. Similar studies by Puspitasari et al [51] shows that they were able to achieved a C p value of 0.20 which indicates 48% increase in the power coefficient. The power coefficient is slightly higher because the operating condition is not the same and the wind speed is 10 m/s as regard to the 4.5 m/s used in this study.…”
Section: Resultssupporting
confidence: 91%
“…For the bare-hybrid VAWT, a maximun C Q value of 0.098 was obtained at λ of 0.88, however when the hybrid VAWT was integrated onto the building rooftop, th C Q values increases from a value of 0.098 to 0.141 at λ of 1.11. that the C Q values of the building integrated hybrid VAWTs increases by 44% which indicate that the building integrated hybrid VAWT has greater torque coefficient compared to the bare-hybrid VAWT. However, similar studies by Puspitasari et al [51] showed that they are able to achieve a C Q value of 0.129 which indicates 29% increase in the power coefficient. In addition, Figure 12 presents the power generated by the building integrated hybrid VAWT and the bare-hybrid VAWT.…”
Section: Resultsmentioning
confidence: 71%
“…Cp is directly dependent on the rotational velocities and, therefore, the moment developed on the blades. The power coefficient is directly proportional to the moment coefficient (Cm) and tip speed ratio (TSR), denoted as λ. TSR is the ratio of the characteristic moment arm length (R blade ) multiplied by the rotational speed of the blade (Ω) to the corresponding wind velocity (V), and it is calculated using Equation (7).…”
Section: Cp =mentioning
confidence: 99%
“…Savonius turbines are notable for their self-starting nature thanks to their high torque at lower speeds. This feature makes them suitable for conditions with low wind speeds [7]. However, despite high starting torque, Savonius turbines have lower efficiency compared to Darrieus turbines, which are typical lift-type airborne wind turbines [8].…”
Section: Introductionmentioning
confidence: 99%
“…However the main disadvantage of the vertical-axis turbine is a low coefficient of performance (CP) [4]. In an effort to improve the coefficient of performance, researchers have tried to modify the blade shape of vertical-axis turbine to be helical-blade [5], trapezoidal-blade [6], contra-rotating blade [7], cavity vane's geometry [8], hybrid Darrieus-Savonius [9], or even to be a blade with flexible material [10].…”
Section: Introductionmentioning
confidence: 99%